ANEMIA IN PRESCHOOL CHILDREN AND ITS ASSOCIATION WITH NUTRITIONAL STATUS AND OTHER FACTORS IN DUHOK PROVINCE, IRAQ - ATRUSHI, AKREM MOHAMMAD; MOHAMMED, BASHAR I.; NAQID, IBRAHIM A.; MIKAIL, DILVEEN SHUKRI; ATAB, DABEN SALAH (Journal of Duhok University, 2023)
Anemia is a very important nutritional issue all over the world. It is most commonly present in preschool children with a prevalence of47.4%. Factors like low socio-economic status, large family size, ignorance and illiteracy are associated with anemia among children less than five years. Aim: To estimate the prevalence of anemia and identify the factors associated with it in children aged 2–5 years. Patients and Methods: A cross sectional study included 798 pre-school children (2–5 years of age) selected from those children who visited health care centres and Heevi Pediatric Teaching Hospital. Dietary, biochemical and anthropometrical, and information were collected through a questionnaire. Children with hemoglobin (Hb) values of <11.0 g/dl were considered anemic. Heights, weights and Body Mass Index [BMI] were measured. Children with [BMI] above 85th centile was considered as overweight and above 95th centile as obese. Data such as past breastfeeding practices, birth weights, time of starting weaning food, duration of breastfeeding, type of weaning food, time of starting infant formula, child’s chronic illness, child’s eating habits, mother’s age, occupation and education were collected. Results: The overall incidence of anemia is 29.8% (238/798). The male: female ratio 1.03:1 in the anemic children. The body weight of the anemic patients was most commonly between 5th and 85th centiles, 155 (65.12%). The most frequent birth weight of the anemic patients was between 2.5 and 4 Kg,191(80.25%). Most of anemic patients had history of breast feeding for equal to or more than six months ,113(47.47%). The weaning foods of most of the anemic patients were cereals, vegetables and fruit 146 (61.34%). About 139 (58.4%) of patients were eating regularly and 156 (65.54%) with the family. Chronic illnesses were present in 63 (26.47%) among anemic patients. About 135(56.72%) of anemic patients had less than three siblings. The age of the mothers was less than 30 years in 112(47.05%). Illiterate mothers were 63(26.47%) among anemic patients and only 18 (7.56%) were employed mothers. The significant association was with the age (p<0.038), the frequency of eating with family (p<0.01) and chronic illnesses (p<0.001). There was a strongly significant correlation between hemoglobin concentration and age group, weight and height. Female was 1.009 times more likely to be anemic. Conclusion: The overall incidence of anemia is 29.8%. The gender, the age of starting weaning foods, the type of weaning foods and the presence of chronic illnesses are significant factors associated with the risk of anemia in the children in Duhok.